1996
DOI: 10.1079/bjn19960164
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin-induced diabetes in rats is associated with impaired metabolic availability of vitamin A (retinol)

Abstract: Using streptozotocin-induced diabetic Wistar rats, studies were camed out to examine the metabolic availability of vitamin A in the plasma, liver and the retina of the eye. Control and diabetic rats were fed ad lib. on a semi-puriiied diet either with or without (basal) vitamin A supplementation, or pair-fed on the basal diet for 4 weeks. Despite the fact that diabetic rats consumed 48 YO more feed, they had lower plasma concentrations of retinol (P < 0.003). The decrease in plasma retinol concentration was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 24 publications
3
56
1
Order By: Relevance
“…Other investigators found that retinol concentrations were signi®cantly decreased in Type 1 (Krempf et al, 1991) and increased in Type 2 diabetes mellitus as compared to control subjects (Krempf et al, 1991;Havivi et al, 1991;Sasaki et al, 1995). Tuitoek et al (1996) reported signi®-cantly lower plasma concentrations of retinol in STZdiabetic Wistar rats which is thought to be a response to diabetes since signi®cantly lower plasma retinol concentrations were also found in pair-feeding and in vitamin A supplemented diabetic rats.…”
Section: Introductionmentioning
confidence: 96%
“…Other investigators found that retinol concentrations were signi®cantly decreased in Type 1 (Krempf et al, 1991) and increased in Type 2 diabetes mellitus as compared to control subjects (Krempf et al, 1991;Havivi et al, 1991;Sasaki et al, 1995). Tuitoek et al (1996) reported signi®-cantly lower plasma concentrations of retinol in STZdiabetic Wistar rats which is thought to be a response to diabetes since signi®cantly lower plasma retinol concentrations were also found in pair-feeding and in vitamin A supplemented diabetic rats.…”
Section: Introductionmentioning
confidence: 96%
“…Although several studies currently focus on the relation between RBP and diabetes, [35][36][37][38][39][40][41][42][43][44][45][46] some results are still conflicting, and this is due mainly to the different methodologies adopted. For this reason, the mechanism responsible for alterations in vitamin A levels and the presence of diabetes has not been entirely elucidated.…”
Section: Vitamin A: Metabolism and Functionsmentioning
confidence: 99%
“…This way, the deficient state observed must be related to the vitamin's impaired transportation. The impairment of its metabolic availability is observed both in decompensated diabetes patients and streptozotocin (STZ) rats-diabetes induced 35,36,38 and Bio-Breed (BB) rats, 37 evidenced through decreased seric retinol levels and seric and hepatic RBP.…”
Section: Vitamin A: Metabolism and Functionsmentioning
confidence: 99%
See 2 more Smart Citations